36. A PROSPECTIVE TRIAL OF RESECTION PLUS SURGICALLY TARGETED RADIATION THERAPY FOR BRAIN METASTASIS. (4th August 2020) - Brachman, David; Nakaji, Peter; Smith, Kris; Youssef, Emad; Thomas, Theresa; Pinnaduwage, Dilini; Rogers, C Leland
Abstract: INTRODUCTION: Achieving durable local control for larger brain metastases remains problematic. Resection (R) alone is typically insufficient. Even with the addition of stereotactic radiation the 12-month recurrence rate for larger lesions (i.e., >2.5–3 cm) is 20% or more in many series. To improve outcomes we designed and prospectively evaluated a permanently implanted radiation device consisting of Cs-131 seeds positioned within a collagen tile (GammaTile, GT Medical Technologies, Tempe AZ). We combined maximum safe resection and collagen tile brachytherapy (CTBT) with the hypothesis that immediate radiation initiation and/or dose intensification could improve outcomes. MATERIALS/METHODS: From 2013–2018 patients undergoing resection with either previously untreated or recurrent brain metastasis were enrolled on a single arm, multi-histology study (ClinicalTrials.gov, NCT#03088579). At resection completion the tumor bed was lined with collagen tiles imbedded with Cs-131, delivering 60–80 Gy at 5 mm depth. The device was designed to prevent direct source-to-brain contact and to maintain inter-source spacing after closure. No additional local therapy was given unless progression occurred. RESULTS: 16 metastases (12 recurrent/4 previously untreated) in 11 patients were treated. Median diameter 3.1 cm, range 1.9–5.1. Histology was 7 breast, 6 lung, and 3 sarcoma. Median age 60 years; 7 females/4 males. Average time for implantation was 5 minutes. At median radiographic follow-up of 9.5 months (range 0.1–25.2) treatment site progression occurred 1/16 (6%) at 10.9 months. Median treatment site time-to-progression (TTP) has not been reached (95% CI, >10.9 months). Median overall survival (OS) 9.3 months. No surgical adverse events occurred. One patient (6.2%) experienced radiation brain changes and was treated medically. CONCLUSION: R+CTBT demonstrated excellent safety and local control outcomes in this single-arm pre-commercial study. The device recently received FDA clearance for use in newly diagnosed and recurrent brain metastasis. Randomized clinical trials vs standard of care treatments are expected to open in 2020.